Teachers’ Nonverbal Cues in EFL Classrooms: Analyzing the Impact of Movement on Student Engagement and Comprehension - Sami'an Wulandari; Amaliah Ramdani; Reskyani Reskyani; Nur Ainun Musa (JELITA, 2024)
The aim of this study examine the effects of teacher movements as a nonverbal communication strategy on student engagement and learning outcomes. The research, conducted at MIN 1 Sinjai, used a qualitative approach that included semi-structured interviews and structured observations to investigate how students perceive the efficacy of their teachers' nonverbal cues, especially in terms of teacher gestures in the classroom. Findings showed that teacher mobility significantly improved attention, participation, and overall classroom dynamics. According to this study, creating a more dynamic and engaging learning environment can be achieved by applying nonverbal communication techniques such as deliberate classroom gestures. Concerning improving teaching methods in the EFL classroom, this observation has useful implications and broadens our understanding of nonverbal communication in educational settings.